Optimalisasi Kewenangan Komisi Pemberantasan Korupsi Dalam Penanggulangan Tindak Pidana Korupsi Pasca Perubahan Undang-Undang KPK - Rahman Rahman (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Corruption remains one of the most serious challenges to law enforcement and good governance in Indonesia, requiring effective institutional mechanisms to prevent and eradicate corrupt practices. This study aims to analyze the duties and functions of the Corruption Eradication Commission (Komisi Pemberantasan Korupsi/KPK), examine the strategies employed by the KPK in handling corruption cases, and identify the obstacles encountered in carrying out its mandate. The research employs a normative juridical approach using statutory, conceptual, and literature review methods to analyze legal regulations and relevant legal doctrines concerning the KPK's authority. The findings indicate that the KPK plays a strategic role through preventive measures, investigation, inquiry, prosecution, coordination, supervision, and public education in combating corruption. However, the effectiveness of these functions is constrained by several factors, including political intervention, overlapping institutional authority, regulatory challenges, and resistance from parties with vested interests. These obstacles may reduce the effectiveness of corruption law enforcement despite the KPK's independent status. The study concludes that strengthening the KPK's institutional independence, enhancing coordination with other law enforcement agencies, and improving the legal framework are essential to ensuring more effective and sustainable corruption eradication efforts in Indonesia